Vontade geral e totalitarismo : uma análise dos aspectos progressistas e conservadores da filosofia política rousseauniana - Ternus, Bruna Fernandes (2021)
Is the Rousseaunian philosophical-political theory, based on the idea of the general will, capable of producing totalitarian regimes? The objective of this research is to identify and analyze conservative and progressive elements in the political philosophy of Jean-Jacques Rousseau, in order to understand possible contradictions and theoretical vacuums that give rise to criticisms of totalitarianism that is considered present in the author's theory. At first, the main arguments developed by the Geneva philosopher in his democratic theory are recovered. Aspects related to the idea of the general will and its exercise in the democratic state will be explored, such as administration and legislation.Then,itisproposedtoexamine the critical arguments developed mainly by Georg W. F. Hegel and Jacob Talmon regarding the possibility of defending totalitarian regimes in the reading of the notion of the general will. At this moment, the aim is to analyze, above all, thecontentofthesecriticisms.Finally, we investigate aspects of Rousseaunian theory that can be identified as progressive or conservative, considering their historical, political and social context. From this analysis itis intended to understand the gaps left by the author in his political investigation,inadditionto determining its avant-garde characteristics.